Replacement of fishmeal by chicken plasma powder in diets for largemouth bass (Micropterus salmoides): Effects on growth performance, feed utilization and health status. (21st August 2019) - Li, Songlin; Ding, Guitao; Wang, An; Sang, Chunyan; Chen, Naisong
Abstract: The present study was conducted to explore the effects of graded replacing fishmeal (0, 50, 100 and 150 g/kg) with chicken plasma powder in diets for largemouth bass, and each diet was fed to triplicate groups of fish (initial weight: 49.50 ± 0.07 g) twice daily. Results showed that specific growth rate was not remarkably reduced until 150 g/kg fishmeal being replaced. Meanwhile, the inclusion of chicken plasma powder led to a significant decrease in feed intake, and the replacement of 150 g/kg fishmeal significantly decreased the apparent digestibility coefficient of protein and essential amino acids, which may account for the lowered protein retention rate and decreased crude protein content of liver and whole body composition. Moreover, the replacement of 150 g/kg fishmeal resulted in a significantly reduced activity of lysozyme, classical complement pathway and respiratory burst, and meanwhile, the red blood cell count and haemoglobin content were also significantly reduced, indicating the impaired health status of fish with high inclusion of chicken plasma powder. In above, approximately 50–100 g/kg fishmeal could be replaced by chicken plasma powder in the diets for largemouth bass.